Mutations in the -10 TATAAT sequence of the gyrA promoter affect both promoter strength and sensitivity to DNA supercoiling. - Straney, R (1994)
Transcription of the gyrA and gyrB genes, which encode the subunits of DNA gyrase, increases in response to DNA relaxation. Previous studies have shown that a small segment of DNA extending from the -10 consensus hexamer to the start of transcription encodes the sequence determinants for this response. In this study, we examined the role of the -10 region in relaxation-stimulated transcription (RST). A synthetic derivative of the gyrA promoter was designed to allow the modular replacement of the -10 region, and mixed-oligonucleotide mutagenesis was used to obtain a collection of promoter mutants. Most substitutions result in a reduction of the promoter's RST response, and some mutations abolish it altogether. We also note that a variety of promoter changes can increase basal expression twofold above that seen for the gyrA promoter, despite sequences changes (up to three bases) which diverge from the consensus TATAAT of the wild-type gyrA hexamer. The wild-type gyrA promoter, however, is the strongest promoter in this collection on a relaxed DNA template and appears to be repressed on a supercoiled template in vivo. Our results are consistent with a mechanism for RST that involves a step in transcription initiation.